2021
DOI: 10.1002/anie.202102098
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐Reversible Surfactant‐Induced Transformation Between Oil‐in‐Dispersion Emulsions and Pickering Emulsions

Abstract: A novel charge-reversible surfactant, (CH 3 ) 2 N-(CH 2 ) 10 COONa, was designed and synthesized, which together with silica nanoparticles can stabilize a smart n-octane-inwater emulsion responsive to pH. At high pH (9.3) the surfactant is anionic carboxylate, which together with the negatively charged silica nanoparticles co-stabilize flowable oil-in-dispersion emulsions, whereas at low pH (4.1) it is turned to cationic form by forming amine salt which can hydrophobize in situ the negatively charged silica na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 43 publications
1
57
0
6
Order By: Relevance
“…We note that some Pickering emulsions can also be stabilized when the interfacial coverage by particles is quite low. [36,37] Here, we believe that only NaDC molecules adsorb at the oil-water interface with silica particles dispersed in the continuous phase between droplets [31][32][33][34][35] producing an oil-indispersion emulsion [35] as shown by the SEM and fluorescence microscopy images (Figures 2 and S7). It was further observed that this strategy of improving the emulsifying ability of BS by addition of silica particles is universal for other BS.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…We note that some Pickering emulsions can also be stabilized when the interfacial coverage by particles is quite low. [36,37] Here, we believe that only NaDC molecules adsorb at the oil-water interface with silica particles dispersed in the continuous phase between droplets [31][32][33][34][35] producing an oil-indispersion emulsion [35] as shown by the SEM and fluorescence microscopy images (Figures 2 and S7). It was further observed that this strategy of improving the emulsifying ability of BS by addition of silica particles is universal for other BS.…”
Section: Resultsmentioning
confidence: 81%
“…The fluorescence image (particles labelled green in Figure S7) also proves the position of the particles is mainly in the aqueous continuous phase. [31][32][33][34][35] This microstructure is different from that of Pickering emulsions stabilized by NaDC and positively charged alumina nanoparticles (Figure 2d), in which particles attach to the oilwater borders forming winkled films on the surfaces of dried oil droplets. We note that some Pickering emulsions can also be stabilized when the interfacial coverage by particles is quite low.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations